Penerapan Strategi Ekspositori untuk Meningkatkan Pemahaman Anak tentang Rukun Islam: Studi Kualitatif di KB Muslimat NU Dologan - Tri Handayani; Latifatus Sa'adah; Helina Himmatul Ulya Lina (Program Studi Pendidikan Guru Pendidikan Anak Usia Dini, Fakultas Tarbiyah dan Keguruan, Universitas Islam Bandung., 2025)
This study aims to describe the application of the expository strategy in teaching the Five Pillars of Islam at KB Muslimat NU Dologan Blora and to analyze the improvement in early childhood understanding following its implementation. The research employed a descriptive qualitative approach with subjects consisting of Group B children aged 3–4 years. The findings show that the application of the expository strategy significantly enhanced children's understanding. Children who previously could not recite the Five Pillars of Islam in sequence began to comprehend both the order and the meaning of each pillar. They were also able to connect the material with their daily experiences, such as performing prayer, fasting, or giving alms. In addition, the children appeared more confident, active, and enthusiastic when engaging in simple practices such as prayer movements and ablution. This study provides practical implications for early childhood educators, demonstrating that the expository strategy can serve as a simple yet effective approach to teaching religious concepts in a structured, concrete manner that aligns with children's developmental stages. Further implications encourage the development of more varied learning media to optimize children's comprehension.